Metformin Restores the Drug Sensitivity of MCF-7 Cells Resistant Derivates via the Cooperative Modulation of Growth and Apoptotic-Related Pathways - Danila Sorokin; Yuri Shchegolev; Alexander Scherbakov; Oxana Ryabaya; Margarita Gudkova; Lev Berstein; Mikhail Krasil'nikov (MDPI AG, 2020)
The phenomenon of the primary or acquired resistance of cancer cells to antitumor drugs is among the key problems of oncology. For breast cancer, the phenomenon of the resistance to hormonal or target therapy may be based on the numerous mechanisms including the loss or mutation of estrogen receptor, alterations of antiapoptotic pathways, overexpression of growth-related signaling proteins, etc. The perspective approaches for overcoming the resistance may be based on the usage of compounds such as inhibitors of the cell energetic metabolism. Among the latter, the antidiabetic drug metformin exerts antitumor activity via the activation of AMPK and the subsequent inhibition of mTOR signaling. The experiments were performed on the ERα-positive MCF-7 breast cancer cells, the MCF-7 sublines resistant to tamoxifen (MCF-7/T) and rapamycin (MCF-7/Rap), and on triple-negative MDA-MB-231 breast cancer cells. We have demonstrated metformin's ability to enhance the cytostatic activity of the tamoxifen and rapamycin on both parent MCF-7 cells and MCF-7-resistant derivates mediated via the suppression of mTOR signaling and growth-related transcriptional factors. The cooperative effect of metformin and tested drugs was realized in an estrogen-independent manner, and, in the case of tamoxifen, was associated with the activation of apoptotic cell death. Similarly, the stimulation of apoptosis under metformin/tamoxifen co-treatment was shown to occur in the MCF-7 cells after steroid depletion as well as in the ERα-negative MDA-MB-231 cells. We conclude that metformin co-treatment may be used for the increase and partial restoration of the cancer cell sensitivity to hormonal and target drugs. Moreover, the combination of metformin with tamoxifen induces the apoptotic death in the ERα-negative breast cancer cells opening the additional perspectives in the treatment of estrogen-independent breast tumors.